(untitled) (Environment & Health, 2020)
Formation of the Special Operation Forces (SOF) in 2016 as an independent part of the Armed Forces of Ukraine was one of the steps in the way of integration of Ukraine to the NATO standards. Process of military personnel training for the Special Operation Forces(SOF) is characterized by the intensive physical loads (often at the limit of the organism’s capabilities) which should be compensated by the adequate nutrition. Objective: We determined the average daily energy losses of the military personnel during the SOF qualification course of training taking into account their physical and psychoemotional loads. Materials and methods: The parameters of the actual average daily energy losses of the military personnel organism during the SOF qualification course of training (Q-course) were measured by the chronometry-and-tabular method of the energy loss calculation. The main exchange parameters of the organism were assessed with the help of the calculation method recommended by the WHO. Results: Average daily energy losses of the military personnel during the Q-course were not stable values and depended on the individual peculiarities of the organism and training events in different phases of training course. The highest average daily energy losses were 6853±737.3 kcal per day during 14-days of the first phase of recruits’ selection (with a maximum parameter of 8648 kcal per day). The highest energy losses made up6277±837.2kcal per day during the final V phase of Q-course. In II, III and IV phases of training course, average daily energy losses were 4900±250kcal per day. Thus, the average daily energy losses of the recruits during Q-course were 554.8kcal per day. Conclusions: Energy losses of more than 8000 kcal per day in some phases of Q-course are a serious problem that may lead to energy deficiency. Such increased energy losses and metabolic requirements of military personnel of the SOF under conditions of high and ultra-high physical loads should be compensated by the corresponding energetic and nutritional value of balanced food intake, adherence to a rational food consumption, which will allow maintaining the daily combat capability of the military personnel at the proper level.